The use of tenofovir and alteration of kidney function in people living with HIV/AIDS (Research, Society and Development, 2022)
This study aims to analyze the alteration in the renal function of PLHIV who used Tenofovir as part of their antiretroviral treatment. This was an observational epidemiological study, through a review of 86 records of PLHIV using Tenofovir, where a survey of data on creatinine values of patients was carried out. A data collection form covering demographic, clinical and laboratory data was used. The estimated Glomerular Filtration Rate was calculated by the CKD-EPI formula. With the results of this study, it was observed that so far, there are no medications free of adverse effects, but it was seen that in addition to monitoring the renal function of patients, it is necessary to prioritize the control of the patient's underlying diseases, as well as the maintenance of an undetectable viral load, a fact that was found in this study, when using TDF as ARVT.